Productivity development in Icelandic : Norwegian and Swedish fisheries - Eggert, Håkan; Tveterås, Ragnar (SNF, 2007)
Several factors contribute to the productivity of nations’ fisheries: Abundance of fish stocks, government regulation of fisheries, and innovations in fishing technologies. We analyze the total factor productivity (TFP) performance of Iceland, Norway, and Sweden from 1973 to 2003. Several competing TFP measures are presented, where some of these account for stock changes and product quality differences between countries. The productivity performance of the three countries is affected by the choice of TFP measure. Although best-practice fishing technologies are widely available on the international market, we do not find uniform evidence of productivity convergence among the three countries over time.